2022
DOI: 10.1111/jdv.17929
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of atopic dermatitis among young adult females and males—report from the Swedish population‐based study BAMSE

Abstract: Background There is limited knowledge regarding prevalence and characteristics of atopic dermatitis (AD) among young adults in the general population. Objectives To study AD among young adults in a Swedish population‐based birth cohort, with a particular focus on prevalence, sex differences including risk for AD at different ages, disease course and characteristics of AD at 24 years. Methods The BAMSE cohort includes 4089 individuals who have been followed regularly from birth to age 24 years regarding AD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
4
22
2
Order By: Relevance
“…2 One reason for the difference in reporting might be the missing detection of mild or minimal current AD cases in a general practice setting.In regard to adult-onset AD, Johansson et al identified 16.9% AD patients who presented with AD for the first time at the 24-year follow-up. 2 This figure matches well with data from a meta-analysis published in 2019. 4 In summary, Johansson et al 2 have to be congratulated for adding further data on AD at 24 years of age in regard to different aspects, including 12-month prevalence, point-prevalence, severity assessment (POEM), adult-onset, sleep affection, IgE sensitization and sex distribution.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…2 One reason for the difference in reporting might be the missing detection of mild or minimal current AD cases in a general practice setting.In regard to adult-onset AD, Johansson et al identified 16.9% AD patients who presented with AD for the first time at the 24-year follow-up. 2 This figure matches well with data from a meta-analysis published in 2019. 4 In summary, Johansson et al 2 have to be congratulated for adding further data on AD at 24 years of age in regard to different aspects, including 12-month prevalence, point-prevalence, severity assessment (POEM), adult-onset, sleep affection, IgE sensitization and sex distribution.…”
supporting
confidence: 86%
“…In regard to adult‐onset AD, Johansson et al . identified 16.9% AD patients who presented with AD for the first time at the 24‐year follow‐up 2 . This figure matches well with data from a meta‐analysis published in 2019 4 …”
supporting
confidence: 85%
See 2 more Smart Citations
“…Although it is still considered primarily a paediatric problem, more and more studies are indicating a high prevalence rate in adults as well. In fact, as shown by a recent study on atopic dermatitis prevalence in a birth cohort at the age of 24, 1 researchers found a 12‐month prevalence of 17.8% in the Swedish BAMSE cohort and, within this group, 16.9% reported experiencing atopic eczema for the first time from the age of 23 onwards.…”
mentioning
confidence: 78%